Pengaruh Pendidikan Keuangan di Keluarga Pengalaman Bekerja Teman Sebaya dan Pembelajaran di Perguruan Tinggi terhadap Literasi Keuangan - Arif Kurniawan; Ratih Kusumawardhani; Risal Rinofah (Universitas Batanghari, 2022)
This study aims to determine the effect of financial education in the family, work experience, peers and learning in college on the financial literacy of students of the Faculty of Economics, Universitas Sarjanawiyata Tamansiswa. Respondents from this study amounted to 100 respondents who came from FE UST students. The method used in this study uses quantitative methods. While the data analysis methods used in this study include descriptive analysis, validity and reliability tests, and multiple regression tests with the help of the SPSS 25 program. The results of this study indicate that financial education in the family has a positive and significant effect on financial literacy, work experience has a positive effect. and significant on financial literacy, peers do not have a significant positive effect on financial literacy, and learning in college has a positive and significant effect on financial literacy.